NILAI PENDIDIKAN KARAKTER DALAM GEGURITAN KI BALIAN BATUR - Apriani, Ni Wayan (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2020)
One of the goals to be achieved in an education both in formal and informal education is character building. The characters discussed are those related to morals, morals, and personality. It is called character when something is done with awareness and conviction and has become a habit. In simple terms, character education is to educate the awareness, belief and habituation of a person related to character / character / morals / personality. As a traditional literature, Geguritan Ki Balian Batur contains many values of life, one of which is the value of character education. By reading the geguritan text, readers will not only be entertained by the aesthetic strains of the tembang but also learn about how the value of character education is applied in real life. The values of character education contained in Geguritan Ki Balian Batur include: (1) religious, (2) national spirit, (3) respect for achievement, (4) peace-loving, (5) social care, and (6) responsibility. With the many values of character education in this geguritan, the authors suggest that educators and parents can use it as a learning medium considering that currently children are experiencing a moral crisis.